2017
DOI: 10.3389/fcimb.2017.00059
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen Reveals Novel Targets to Render Pseudomonas aeruginosa Sensitive to Lysozyme and Cell Wall-Targeting Antibiotics

Abstract: Pseudomonas aeruginosa is capable of establishing airway infections. Human airway mucus contains a large amount of lysozyme, which hydrolyzes bacterial cell walls. P. aeruginosa, however, is known to be resistant to lysozyme. Here, we performed a genetic screen using a mutant library of PAO1, a prototype P. aeruginosa strain, and identified two mutants (ΔbamB and ΔfabY) that exhibited decrease in survival after lysozyme treatment. The bamB and fabY genes encode an outer membrane assembly protein and a fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Like in Kp , several porins as well as the autotransporter invasin were significantly decreased in Ye . Another study addressing the role of BamB in Pa PAO1 already showed that bamB deletion also leads to sensitization against lysozyme, vancomycin and cefotaxime (Lee et al, 2017), which could be confirmed in our study. However, in contrast to Ye or Kp , neither increased sensitivity against human serum nor attenuation of virulence was observed.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Like in Kp , several porins as well as the autotransporter invasin were significantly decreased in Ye . Another study addressing the role of BamB in Pa PAO1 already showed that bamB deletion also leads to sensitization against lysozyme, vancomycin and cefotaxime (Lee et al, 2017), which could be confirmed in our study. However, in contrast to Ye or Kp , neither increased sensitivity against human serum nor attenuation of virulence was observed.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, BamB may contribute to the assembly of porins and autotransporters in Pa , but in contrast to the function of BamB in Kp or Ye , the rather mild phenotypes we found upon deletion of bamB in Pa PA14 do not justify considering it as a promising target for drug development from our point of view. Nonetheless, given the results that have been obtained with e.g., Pa PAO1 and Salmonella (Namdari et al, 2012; Lee et al, 2017), it cannot be ruled out that the importance of BamB for OM composition and consequently the resulting phenotypes might vary significantly between strains and species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been reported for P . aeruginosa when exposed to different antibiotics, including treatment with CIP (Day et al ., ; Lee et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that a bamB mutant in reference strain PAO1 is highly sensitive to antibiotics (especially those targeting cell wall synthesis) and lysozymes [ 27 ]. Therefore, we tested the resistance of the STM PALES_11731 mutant to piperacillin (a β-lactam antibiotic), tobramycin (an aminoglycoside antibiotic) and lysozymes.…”
Section: Main Textmentioning
confidence: 99%